Legal Framework For Crypto Asset Trading As An Effort To Protect Consumers In Indonesia - Otih Handayani; Esther Masri; Panti Rahayu; Achmad J. Pamungkas; Muhammad Azam (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Cryptocurrency has emerged as a disruptive and revolutionary asset in the global financial landscape, transforming how individuals and organizations conduct financial transactions. In Indonesia, cryptocurrency is prohibited as a means of payment but is permitted as a digital asset (crypto asset) that can be traded. Crypto assets operate through a decentralized system that lies outside the control of the government and centralized authorities. As of October 2024, the number of crypto asset consumers in Indonesia reached 21.27 million, and throughout 2024, it has contributed to the development of the digital financial services sector, with transactions amounting to IDR 650.61 trillion. Volatility, illegal crypto asset traders, hacking, and scamming are among the key issues in crypto asset trading. This research is a doctrinal/normative legal study using a statutory approach. It is based on a literature review and analyzed qualitatively. The findings show that the Ijtima Ulama of the National Fatwa Commission VII in 2021 and OJK Regulation (POJK) No. 27 of 2024 indicate that the government is getting involved in crypto asset trading. However, several weaknesses in the POJK, including the unclear position of individual consumers and the absence of mandatory risk mitigation requirements for traders, may result in the lack of security guarantees for consumer crypto assets.